INTERNAL BALANCING OF INDUSTRIAL COMPLEX: PRINCIPAL NEED AND EVALUATION METHODOLOGY - Valentina Parakhina; Pavel Timoshenko (Вестник Северо-Кавказского федерального университета, 2022)
The internal balance of the development of the industrial complex is related to the consistency of the changes occurring in it, which can be characterized using the ranked system of indicators and the concordance coefficients of Candell and Spearman to assess the consistency of actual and normative ranks. In each of these sets, the indicators were assigned regulatory ranks, which became the basis for further research on the balance of the Russian industrial complex for 2011-2015.